2008
DOI: 10.1158/1535-7163.mct-08-0251
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis is strongly reduced by the matrix metalloproteinase inhibitor Galardin in the MMTV-PymT transgenic breast cancer model

Abstract: Matrix metalloproteinases (MMP) have several roles that influence cancer progression and dissemination. However, low molecular weight metalloproteinase inhibitors (MPI) have not yet been tested in transgenic/spontaneous metastasis models. We have tested Galardin/GM6001, a potent MPI that reacts with most MMPs, in the MMTVPymT transgenic breast cancer model. We followed a cohort of 81 MMTV-PymT transgenic mice that received Galardin, placebo, or no treatment. Galardin treatment was started at age 6 weeks with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 42 publications
(69 reference statements)
4
34
0
Order By: Relevance
“…In marked contrast, NM supplementation induced intense internal collagen IV production, forming a dense fibrous network of collagen IV that surrounded live nucleated cells and large amounts of necrotic cellular debris. The fibrotic response observed with NM supplementation is similar to the collagen deposition reported by Almholt et al when investigating an experimental pan-MMP inhibiting drug, which was shown to decrease metastatic burden 100-fold (21). Furthermore, tumors from the control group mice exhibited little to no collagen I expression either internally or in the fibrous capsule.…”
Section: Discussionsupporting
confidence: 82%
“…In marked contrast, NM supplementation induced intense internal collagen IV production, forming a dense fibrous network of collagen IV that surrounded live nucleated cells and large amounts of necrotic cellular debris. The fibrotic response observed with NM supplementation is similar to the collagen deposition reported by Almholt et al when investigating an experimental pan-MMP inhibiting drug, which was shown to decrease metastatic burden 100-fold (21). Furthermore, tumors from the control group mice exhibited little to no collagen I expression either internally or in the fibrous capsule.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, this approach is suited to observing the promotion of cell migration by chemoattractants ( Figure 2) and to assessing the inhibition of cell migration by pharmaceuticals such as galardin. Galardin is a known as MMP inhibitor (11)(12)(13) and is reported to prevent invasion and metastasis (14,15) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various quantitative methods of assessing cell migration and invasion have been reported (8,(14)(15)(16)(17)(18)(19). Some of these methods facilitate the fl uorescenceassisted quantification or real-time observation of migrating cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lung tumors developed in MMTV-PyMT MMP-9 wild type mice are larger in size and are more highly vascular compared to those tumors that developed in MMTV-PyMT MMP-9 null mice. Thus, the data presented here is consistent with the above studies and demonstrate that down regulation of MMP-9 by AM9D also affects tumor growth via inhibiting angiogenesis and inducing apoptosis ( Our results are consistent with those of Almholt, et al [67] which showed that the broad-spectrum MMP inhibitor Galardin/GM6001, significantly reduced primary mammary tumor growth by 50% and reduced lung metastasis by more than 100-fold in the MMTV-PyMT model. However, contrary to broad-spectrum MMP inhibitors, including GM6001, AM9D treatment specifically down regulates MMP-9 without affecting the expression of other members of the MMP family ( Figure 1-3b and 1-3c).…”
Section: Discussionsupporting
confidence: 93%
“…More than 90% of mice develop pulmonary metastasis by 100 days [62]. More importantly, the mammary adenocarcinomas exhibit changes in biomarkers and expression patterns of various MMPs similar to those observed in human breast cancer patients [59,[63][64][65][66][67]. Therefore, this model was chosen to ascertain the role of AM9D as a pharmacologic inhibitor of MMP-9.…”
Section: Mmtv-pymt Transgenic Mammary Tumor Modelmentioning
confidence: 99%